Studi Komparasi Minat Berwirausaha Pada Mahasiswa Prodi Administrasi Bisnis dan Prodi Manajemen Angkatan 2019 Untag Surabaya Ditinjau Dari Pendidikan Kewirausahaan dan Lingkungan Keluarga - Watusslikha, Alifia Rukmana; Mulyati, Awin; Pratiwi, Ni Made Ida (Research Journal of Social Science and Economics, 2023)
The research was conducted with the aim of knowing the differences in Entrepreneurial Interests for Students of the Business Administration Study Program and Management Study Program Class of 2019 Untag Surabaya in terms of Entrepreneurship Education and Family Environment. This research uses a quantitative approach with a comparative research type. Comparative research is a type of research used to compare two or more types of groups. Respondents in this study were 80 students consisting of 40 business administration study program students and 40 management study program students. Data collection uses the probability sampling method (random sampling) because it is certain that students of the Business Administration Study Program and Management Study Program Class of 2019 Untag Surabaya have taken the Entrepreneurship course. Data were obtained by distributing questionnaires containing several statements to the target respondents by measuring them using a Likert scale to find out whether the respondents agreed/disagreeed. The data that has been collected is then analyzed using a homogeneity test with the aim of knowing whether the two groups have the same variance or not. followed by a test of two different means (Independent Sample T Test) to find out whether there is a difference between the two sample groups. The results showed that there was no difference in Entrepreneurial Interest in Students of Business Administration Study Program and Management Study Program Batch 2019 Untag Surabaya in terms of Entrepreneurship Education and Family Environment. Keywords: Entrepreneurship Education, Family Environment, Interest in Entrepreneurship